A Competency Model for the Selection and Performance Improvement of Project Managers in Collaborative Construction Projects: Behavioral Studies in Norway and Finland - Moradi, Sina; Kähkönen, Kalle; Klakegg, Ole; Aaltonen, Kirsi (Buildings (Basel), 2021)
Collaborative work practices are getting more common in construction projects. Consequently, new project delivery models have emerged and new practices have also entered the world of traditional delivery models. The resultant collaborative construction projects provide a different working environment compared to the traditional construction delivery models. This different environment seems to require project managers with certain types of competencies, but there is currently very limited research-based knowledge concerning this subject. This study aims at identifying such competencies, which project managers of collaborative construction projects need to possess to succeed. For this purpose, a human behavioral approach was employed where project managers’ behavior in their everyday work was the main source for understanding their competencies. Accordingly, the survey strategy was utilized, where a self-evaluation questionnaire was sent to 33 project managers of collaborative construction projects, and a response rate of 73% was achieved. The findings present four groups of competencies within a matrix model, structured based on their contribution to project managers’ successful performance in collaborative construction projects and the degree to which they can develop those competencies. The developed model can provide a baseline for selecting project managers and for enhancing the performance of the current ones.